2011
DOI: 10.1530/eje-10-0825
|View full text |Cite
|
Sign up to set email alerts
|

Q192R polymorphism of the paraoxonase-1 gene as a risk factor for obesity in Portuguese women

Abstract: Introduction: Obesity became a major public health problem as a result of its increasing prevalence worldwide. Paraoxonase-1 (PON1) is an esterase able to protect membranes and lipoproteins from oxidative modifications. At the PON1 gene, several polymorphisms in the promoter and coding regions have been identified. The aims of this study were i) to assess PON1 L55M and Q192R polymorphisms as a risk factor for obesity in women; ii) to compare PON1 activity according to the expression of each allele in L55M and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…Finnish [15], British [16] and German [17] studies showed also similarity. Our data of Hungarian population is nearly the same as Portuguese [18], Turkish [19] and Irish [20] populations. There is a large contrast between European and Asian data.…”
Section: Discussionsupporting
confidence: 69%
“…Finnish [15], British [16] and German [17] studies showed also similarity. Our data of Hungarian population is nearly the same as Portuguese [18], Turkish [19] and Irish [20] populations. There is a large contrast between European and Asian data.…”
Section: Discussionsupporting
confidence: 69%
“…Recent studies indicate that HDL-associated PON1 may be involved in the pathogenesis of metabolic syndrome and obesity by demonstrating low A-ase, P-ase (6) and L-ase (18) activities and by presenting some associations with less active PON1 gene variants in obese individuals (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…HDLassociated PON1 hydrolyzes paraoxon, organophosphorus compounds, unsaturated aliphatic esters and aromatic carboxylic esters (2,5). PON1 enzymatic activity is characterized by large interindividual variation and its low values predict a high risk of developing diseases involving oxidative damage and lipid peroxidation (5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the 192R isoform has higher lactonase activity and higher binding affinity to HDL and hydrolyzes paraoxon faster compared to the 192Q isoform, whereas the 192Q isoform exhibits lower stability and hydrolyzes diazoxon faster [Bhattacharyya et al 2008;Gaidukov et al 2006;Gupta et al 2011;Veiga et al 2011]. In comparison, the 192Q isoform of PON1 is more efficient in reducing total lipidperoxide content and therefore shows higher antioxidant effects [Mackness et al 1998b].…”
Section: Introductionmentioning
confidence: 99%